Meşrutiyet Döneminde Asker-Vatandaş Yetiştirme Anlayışı Çerçevesinde Paramiliter Gençlik Örgütleri / Paramilitary Youth Organizations within the Framework of Training Citizen-Militia Conception in the Second Constitutional Period - Çelebi, Nurhayat; Asan, Hatice Tezer; Asan, Engin (Journal of History Culture and Art Research, 2018)
Abstract In this study, the struggle against paramilitary organizations and associations founded during the Second Constitutional period when the conception of nation-state and the concept of citizen-militia gained momentum in European states has been scrutinized. The research is a qualitative study based on a document analysis. After the traumas of wars in the Ottoman Empire, which entered the process of rapidly losing the lands spreading over three continents, the education mentality has been re-examined within the framework of citizenship conception. In addition to these inquiries and innovations, which began especially in the military area, they also manifested themselves with educational programs and schools centered on military regimes. This paradigm shift, which accelerated especially with the 18th century, soldier-son themed citizen perception and the current dominant patriarchal moral shave had reflections on education mentality and practice of social structure organized by the state and they turned into bringing up sons as warriors, power-owners and citizens ready to sacrifice for their motherland. Öz Bu çalışmada, Ulus-devlet anlayışının ivme kazandığı Avrupa devletlerinde vatandaş-asker anlayışı ve uygulamasının ön plana geçtiği II. Meşrutiyet yıllarında açılan paramiliter örgüt ve derneklere ilişkin çabalar mercek altına alınmıştır. Araştırma doküman incelemesine dayalı nitel bir çalışmadır. Üç kıtaya yayılan topraklarını hızla kaybetme sürecine giren Osmanlı İmparatorluğu’nda yaşanan savaş travmalarından sonra vatandaş kavramı çerçevesinde eğitim anlayışı yeniden gözen geçirilmiştir. Özellikle askeri alanda başlayan bu sorgulamalar ve yenilik arayışlarının yanı sıra, yine askeri düzenlemeleri merkeze alan eğitim programları ve okulları ile kendini açıkça belli etmiştir. Özellikle 18. Yüzyılla birlikte hız kazanan bu paradigma değişimi, asker-evlat ana temalı vatandaş algısı ile halihazırda baskın ataerkil değerler, sosyal yapının bu kez devlet eliyle organize edilen eğitim anlayışı ve uygulamalarına yansımış; “savaşçı, erk sahibi, vatana kendini feda etmeye hazır” –özellikle erkek- evlatların yetiştirilmesine dönüşmüştür.